Effects Of Cellulose Bridging Phenomenon On Breakdown Voltage And Conduction Current Characteristics In Mineral And Ester Transformer Oils - Zainoddin, Muhamad Hafiy Syazwan (2018)
Dielectric liquid plays a vital role in High Voltage (HV) system. This liquid is used as an insulator, as well as in cooling method to dissipate heat generated from transformer windings and cores. Failure to maintain the condition for insulation will lead to transformer failure and significant losses of power electricity system. Almost 30% of the transformer failures from all over the world are caused by insulation failure and most of the cases are due to contaminant presence in the dielectric liquid. One of the major defects caused by the contamination is bridge phenomenon, potentially act as a conducting current path between two different potentials and lead to insulation failure. In order to understand the bridging phenomenon effects on dielectric liquid, this thesis presents the investigation on the breakdown voltage (BdV) and conduction current path characteristics in three types of dielectric liquid namely Gemini X (mineral oil), MIDEL 7131 (synthetic ester) and MIDEL eN (natural ester) contaminated with cellulose particles. These experiments were conducted in test cell using sphere-sphere electrode configuration under DC voltage stress. Three different contaminant sizes, i.e. 100, 300 and 500 µm, and three different gap distances, i.e. 10, 15 and 20 mm with two types of experiment conditions, i.e. stirred and without stirred were used in BdV and conduction path experiments. Three voltage levels were used for conduction current path experiment, i.e. 2, 7, and 15 kV for 25-minutes and for the BdV experiment, the voltage was applied in steps of 5 kV with a 1-minute interval for each step until BdV occurs or maximum 25-minutes. The formation of cellulose particles bridge have been analysed by taking the time taken for the particles to start attach on the electrodes surface and time taken to completely form cellulose particles bridge between electrodes. The results show that the presence of contaminant in dielectric liquid and the level of dielectric liquid viscosity play important roles in all experiments. In general, the cellulose bridge formation time, conduction current path and BdV increased as the size of particles increased. However, no cellulose bridge is observed when low voltage was applied to lower particle size during conduction current path experiment. In addition, the bridge condition is also different for each experiment, i.e. bridge condition in without stirred condition is always thicker and dense regardless the particle size used and gap distance compared with stirred condition. As a whole, MIDEL eN has a better performance compared to MIDEL 7131 and Gemini X as the BdV recorded is higher regardless the particle size, gap distance and experiment condition. Furthermore, it is obvious that all dielectric samples with contaminant presence will increase the BdV value with no correlation with particle size and gap distance. On the contrary, conduction current path recorded in Gemini X is always the highest which is believed due to the effect of viscosity, as lower viscosity level of dielectric liquid would increase the collation between oil molecules and cellulose particles which contribute to faster bridging formation and higher conduction current path.